Finding research information on the web: how to make the most of Google and other free search tools. (28th March 2013) - Blakeman, Karen
The Internet and the World Wide Web has had a major impact on the accessibility of research information. The move towards open access and development of institutional repositories has resulted in increasing amounts of information being made available free of charge. Many of these resources are not included in conventional subscription databases and Google is not always the best way to ensure that one is picking up all relevant material on a topic. This article will look at how Google's search engine works, how to use Google more effectively for identifying research information, alternatives to Google and will review some of the specialist tools that have evolved to cope with the diverse forms of information that now exist in electronic form.